2022
DOI: 10.3233/wor-211308
|View full text |Cite
|
Sign up to set email alerts
|

An assessment on loss of workforce due to COVID-19 among healthcare personnel: A university hospital experience

Abstract: BACKGROUND: Healthcare personnel are among the COVID-19 risk groups. For this reason, increased absence from work affects the loss of labor. OBJECTIVE: This study aimed to evaluate the workforce loss amongst health personnel working in our hospital due to COVID-19 in a one-year period. METHODS: Workforce loss of healthcare workers was assessed via absenteeism and life expectancy. Loss of workforce for COVID-19 PCR positive or PCR negative but CT findings compatible with COVID-19 and personnel with high-risk ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Nineteen articles reporting original data on COVID-19-associated absenteeism among HCP were identified [3,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. The characteristics of these articles and their main findings are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nineteen articles reporting original data on COVID-19-associated absenteeism among HCP were identified [3,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. The characteristics of these articles and their main findings are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, in a teaching hospital in Brazil, younger cleaning staff took more sick leaves due to suspected COVID-19 compared with older staff [30]. In contrast, significantly higher absenteeism rates for HCP older than 40 years were recorded in a hospital in Turkey compared with younger HCP [23].…”
Section: Absenteeism In the First Year Of The Covid-19 Pandemicmentioning
confidence: 94%
“…Likewise, another study showed that on average, HCWs took 12.5 absent days after having a COVID-19 infection ( 38 ). A study in Turkey ( 39 ) showed that there was a total lost time from work of 14,635 days in their HCWs across the span of 1 year (2020–2021). A study in Brazil ( 40 ) showed that absenteeism due to a medical reason increased from 633 individuals to 837 from 2019 to 2020, in which nursing assistants were reported to have the highest frequency of medical leave.…”
Section: Discussionmentioning
confidence: 99%
“…A group of researchers from Turkey, based on a study conducted during 2020/2021 at the University Hospital of Istanbul among medical staff taking care of patients with COVID-19, confirmed an increase in absenteeism and loss of manpower. The researchers did not take shift work into account [ 13 ].…”
Section: Introductionmentioning
confidence: 99%